Inventory Information System Development to Improve Goods Data Collection Process - Silvia Apriyanti; Devi Yurisca Bernanda (Universitas Bina Darma, 2023)
The study subject is a company operating in the iron industry, where its business processes are hampered by challenges in effectively managing its inventory. The existing inventory system is characterized by disorganized stock storage within the warehouse, leading to difficulties in monitoring stock availability. Moreover, the tracking of incoming and outgoing goods lacks consistency, further impacting inventory accuracy. Additionally, the generation of reports relies on manual processes, resulting in prolonged report completion times. To address these issues, this study developed a comprehensive inventory website aimed at enhancing the company's inventory management. The website serves as a platform to monitor incoming and outgoing goods, providing real-time visibility into stock levels. The development approach chosen for this endeavor was the Waterfall method, known for its systematic and structured nature. The outcomes of this research encompass the successful creation of an inventory website that proficiently records and manages incoming and outgoing goods data. The website also facilitates the automated generation of accurate purchase and sales reports, significantly reducing the time required for this task. Thorough testing, employing blackbox testing techniques, confirmed the robust functionality of the website, with all components performing effectively.